Enhancement of Rivest Shamir Adleman (RSA) Key Generation Utilizing the Diffie-Hellman Algorithm for PDF File Security - Murti, Maliyah; Rahmadani, Rahmadani; Puspadini, Ratih (Politeknik Negeri Lhokseumawe, 2025)
The development of digital technology poses challenges to data security, especially in frequently used PDF files. Cryptography can be used for data security. The conventional RSA algorithm with a static public key is vulnerable to attacks. This study integrates Diffie-Hellman to generate a shared key as a public exponent (e) in RSA, making key generation more dynamic and secure. The method includes system analysis, a combined implementation of Diffie-Hellman and RSA, and testing on PDF files. Data is converted to decimal numeric format before encryption and decryption. The encryption is stored in (*.txt), decryption returns the file to the original PDF. The results show that the use of a shared key improves security even though the encrypted file size increases by about 4-5 times from the original file. This system is expected to be a better solution for PDF security and modern cryptography.